CONCEPTUALISING THE POTENTIAL OF DIVERSITY: HOW DIVERSE TEAMS CREATE INNOVATION AND GAIN A COMPETITIVE EDGE - Thilageswary Arumugam; Siva Chandren Kandasamy, (Malaysian Journal of Business and Economics (MJBE), 2024)
This paper seeks to present a literature review on diversity and inclusion inside organisations regarding innovation. Evidence suggests that diverse teams can tap into various viewpoints to generate significant competitive advantages by enhancing strategic customer relations and market orientation. Unique teams may have challenges in decision-making, but management practices positively influence facts, creativity, and quality work. This paper briefly reviews diversity and inclusion, whereby diversity merely brings in a mix of different people, inclusion effectively uses these diverse groups correctly. The article concludes by pointing out that it is not only the extension of a hand of fellowship to minorities but also the call for them to grasp the chance and positively impact the achievement scores of the organisations.